Perspectives on and Precautions for the Uses of Electric Spectroscopic Methods in Label-free Biosensing Applications - Garrote, Beatriz L. [UNESP]; Santos, Adriano [UNESP]; Bueno, Paulo R. [UNESP] (American Chemical Society (ACS), 2019)
Label-free approaches for molecular diagnostic applications are appealing because of their inherent point-of-care advantages. Nonetheless, technical challenges impose a limit on the use of these methods as will be discussed in this paper. Electrochemical spectroscopic methods, such as impedance and impedance-derived methods, are highly effective in the development of label-free diagnostic assays, but they require careful control of the dynamics of the sensing interface. We herein report the strength and challenges of the current methodologies associated with the applications of impedance and impedance-derived methods by focusing on their principles of operation. We demonstrate that the uses of their potentialities are not based on the know-how of these methods, but on how to combine the spectroscopic features with the required chemical design for the associated sensing interfaces. Predominantly, we illustrate how to use the resistive and capacitive terms of the interface to improve its sensitivity to the target. For instance, with the proper signal amplification strategy, limitations related to target-to-receptor size ratio can be overcome. The target-to-receptor ratio is one of the difficulties that we use as an example to illustrate how the sensing of an electric signal can be improved by controlling the properties of the interface on the nanometer scale.
Keywords: biosensors; capacitive biosensors; charge transfer resistance; electrochemical capacitance; electrochemical impedance spectroscopy; label-free diagnostic; molecular assaying; point-of-care diagnostics